Parkinsonism following basal ganglia infarction in Dengue fever - Manappallil, Robin George; Kumar V.G., Pradeep; Rao K.S., Apurva (Asian Journal of Medical Sciences, 2019)
Dengue fever is an acute febrile viral illness characterized by severe headache, myalgia, arthralgia, rashes, leucopenia and thrombocytopenia. Patients may face haemorrhagic complications like gastrointestinal bleeding, intracranial haemorrhage, menorrhagia, hematomas, hematuria and massive epistaxis. Ischemic stroke in dengue fever is a rare scenario; and Parkinsonism following basal ganglia infarction in dengue fever, to the best of our knowledge, has not been reported yet.